Beyond religious freedom: Asia-Pacific engagements in conversation with Elizabeth Shakman Hurd. Issue 1 (2nd January 2018) - Rees, John A.; Smartt, Tim
Abstract: This article frames religion as a contested category in the study of political practice and serves as an introduction to a special issue of the JRPP that interrogates the politics of religious freedom in contexts of the Asia-Pacific. Mavelli and Petito's depiction of two modes of postsecularism (2012) – summarised as the mode of religious resilience and the mode of radical critique – allows further consideration of contrasting assumptions shaping current debates about religion and politics. We suggest that the recent and influential scholarship of Elizabeth Shakman Hurd can be aligned with the mode of radical critique, noting the influence of Beyond Religious Freedom (2015) as establishing a platform for further critical studies of the political use of religion in diverse global contexts. New essays drawn from settings across the Asia-Pacific – Malaysia, Sri Lanka, Myanmar, Australia, United States, East Asia – are situated within this broader discourse and in conversation with Hurd's work. In addition, the inclusion of perspectives that instantiate the mode of religious resilience reestablish the interlocution between the two modes of postsecularism and the contested nature of religion as a category of political practice research.